The Effect Of Incentives On Improving Organization Performance: Field Study On Lattakia Textile Company - فايز غزال (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aims at finding out the effect of incentive schemes, both moral and material, on improving organizational performance (Lattakia Textile Company), using descriptive methodology and analytical approach. Research sample consists of (235) questionnaires distributed among staff, (3) rejected for being invalid and (232) have been valid to use. The data statistical analysis has been done using SPSS program version 25, and the study has reached to the following results: There is a moral relationship between incentive scheme and organizational performance. There is a moral relationship between material and moral incentives on one side and organizational performance on the other taking care about the material incentives are more important than moral incentives from the study sample point of view in Lattakia Textile Company. The research recommends giving more attention to the concept of incentive whether material or moral as it has direct influence on organizational performance, and designing material incentive scheme that corresponds with the unstable economic changes , in addition to reconsidering the daily ration of incentive from (26) to (500) S.P. as a minimum in view of low exchange rates so that it becomes a real incentive, and expanding more with encouraging team spirit within the work team in order to encourage staff to work, as well as adding other advantages for workers such as organizing recreational trips for distinguished staff and their intellectual children, and sharing school expenses with them, in addition to putting illuminated bulletin boards inside the organization listing the names of distinguished workers, and seeking to design an effective performance evaluation system which helps to identify and spread strong points on one hand and identify and treat weak points , turning them to strong points.